2019
DOI: 10.1097/mpg.0000000000002364
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Interventions in Pediatric Pancreatitis

Abstract: Objective: Despite the fact that pediatric pancreatitis is an uncommon disease, its prevalence has increased in recent years. Nevertheless, until 4 years ago, the lack of nutritional guidelines for pediatric pancreatitis was evident, with all recommendations being based on clinical practice guidelines (CPGs) for adults. The aim of the present study was to review and critically appraise guidelines for the medical nutrition therapy (MNT) of pediatric pancreatitis. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Several recent studies have suggested that nutrition guidelines are not adequately adhering to the standards for CPG development . This is why a collective initiative to ameliorate nutrition guideline quality has been proposed, using novel tools such as the NutriRECS .…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have suggested that nutrition guidelines are not adequately adhering to the standards for CPG development . This is why a collective initiative to ameliorate nutrition guideline quality has been proposed, using novel tools such as the NutriRECS .…”
Section: Discussionmentioning
confidence: 99%
“…I did identify 5 other similar systematic reviews that have been published by this group in the past 2 years, covering the topics of adults with severe burns, 4 celiac disease, 5 pediatric pancreatitis, 6 gestational diabetes, 7 and cirrhosis 8 . In all of these reviews, as was reported in this one as well, the guidelines were often found to be poorly developed and reported, as determined by the AGREE II criteria.…”
mentioning
confidence: 98%